Stadium as a Landmark: Captain I Wayan Dipta Stadium Tour Program as a New Attraction for Sports Tourism in Bali - Prayoga, I Putu Satria; Putra, I Nyoman Darma; Suardiana, I Wayan (LP2M ISBI Bandung, 2025)
The Bali United Football Club's Captain I Wayan Dipta Stadium Tour Program, which was initiated recently, has started attracting tourists. This program, which has been running since 2019, is particularly popular among football fans. This study aims to explore the development of the Captain I Wayan Dipta Stadium Tour using a qualitative method. Data were collected through observation and interviews and analyzed using commodification theory. The research findings conclude that the development of the Captain I Wayan Dipta Stadium Tour, which began with Bali United's arrival in Bali and the renovation and beautification of the stadium, not only increased the stadium's popularity but also added a new tourist attraction to Bali's sports tourism. Bali's tourism, which is dominated by natural and cultural attractions, has expanded to include sports tourism in the form of stadium tours.